FIGURE 2. A–C in Some hydrozoans (Cnidaria) from King George Island, Antarctica - Galea, Horia R.; Schories, Dirk (Icarus, 2012)
FIGURE 2. A–C: Hydractinia angusta Hartlaub, 1904 — fragment of colony showing gastro-, gonozooid, and spine (A); gonozooid (B); cnidome (C). D: Opercularella sp. — hydrothecate pedicel. E, H: Halecium antarcticum Vanhöffen, 1910 — stem internode (E); gonotheca (H). F, G, I: Halecium delicatulum Coughtrey, 1876 — specimen MHNG-INVE-26669, showing hydrothecae (F), stem internodes (G), and a female gonotheca (I). J, K: Halecium ovatum Totton, 1930 — fragment of stem showing branching pattern (J); female fonotheca (K). L, M: Antarctoscyphus elongatus (Jäderholm, 1904) — internodes with hydrothecae (L); gonotheca (M). N–P: Antarctoscyphus spiralis (Hickson & Gravely, 1907) — internode with hydrotheca (N); hydrothecal aperture in frontal view, showing intrathecal cusps (O); gonotheca (P). Q–S: Sertularella gaudichaudi (Lamouroux, 1824) — fragment of stem (Q); hydrotheca (R); female gonotheca (S). T, U: Symplectoscyphus cumberlandicus (Jäderholm, 1905) — fragment of stem (T); female gonotheca (U). V, W: Symplectoscyphus glacialis (Jäderholm, 1904) — fragment of stem (V); gonotheca (W). X–Z: Symplectoscyphus vanhoeffeni Totton, 1930 — fragments of stems from Stn. Ant.06/2011 (X) and Stn. Ant.12/2010 (Y); gonotheca from material from Stn. Ant.06/2011 (Z). Scale bars: 10 µm (C), 100 µm (O), 300 µm (D, R), 400 µm (B), 500 µm (E–I, K–N, P, V–Z), 800 µm (J), 900 µm (T), 1 mm (A, Q, S, U). Published as part of Galea, Horia R. & Schories, Dirk, 2012, Some hydrozoans (Cnidaria) from King George Island, Antarctica, pp. 1-21 in Zootaxa 3321 on page 8, DOI: 10.5281/zenodo.213236